Cell-cell interaction in the pathogenesis of inherited retinal diseases - Du, Xue; Butler, Anna G.; Chen, Holly Y. (Frontiers in Cell and Developmental Biology, 2024)
The retina is part of the central nervous system specialized for vision. Inherited retinal diseases (IRD) are a group of clinically and genetically heterogenous disorders that lead to progressive vision impairment or blindness. Although each disorder is rare, IRD accumulatively cause blindness in up to 5.5 million individuals worldwide. Currently, the pathophysiological mechanisms of IRD are not fully understood and there are limited treatment options available. Most IRD are caused by degeneration of light-sensitive photoreceptors. Genetic mutations that abrogate the structure and /function of photoreceptors lead to photoreceptor dysfunction and visual impairment followed by blindness caused by loss of photoreceptors. In healthy retina, photoreceptors structurally and functionally interact with retinal pigment epithelium (RPE) and Müller glia (MG) to maintain retinal homeostasis. Multiple IRD with photoreceptor degeneration as a major phenotype are caused by mutations of RPE-and/or MG-associated genes. Recent studies also reveal compromised MG and RPE caused by mutations in ubiquitously expressed ciliary genes. Therefore, photoreceptor degeneration could be a direct consequence of gene mutations and/or could be secondary to the dysfunction of the interaction partners of photoreceptors in the retina. This review summarizes the mechanisms of photoreceptor-RPE/MG interaction in supporting retinal functions and discusses how the disruption of these processes could lead to photoreceptor degeneration, with an aim to provide a unique perspective of IRD pathogenesis and treatment paradigm. We will first describe the biology of retina and IRD and then discuss the interaction between photoreceptors and MG/RPE as well as their implications in disease pathogenesis. Finally, we will summarize the recent advances in IRD therapeutics targeting MG and/or RPE.